Effect of deproteinization and tubular occlusion on microtensile bond strength and marginal microleakage of resin composite restorations (Journal of Applied Oral Science, 2009)
Dentin adhesion procedure presents limitations, especially regarding to lifetime stability of formed hybrid layer. Alternative procedures have been studied in order to improve adhesion to dentin. OBJECTIVE: The aim of this study was to evaluate in vitro the influence of deproteinization or dentin tubular occlusion, as well as the combination of both techniques, on microtensile bond strength (µTBS) and marginal microleakage of composite resin restorations. MATERIAL AND METHODS: Extracted erupted human third molars were randomly divided into 4 groups. Dentin surfaces were treated with one of the following procedures: (A) 35% phosphoric acid gel (PA) + adhesive system (AS); (B) PA + 10% NaOCl + AS; (C) PA + oxalate + AS and (D) PA + oxalate + 10% NaOCl + AS. Bond strength data were analyzed statistically by two-way ANOVA and Tukey's test. The microleakage scores were analyzed using Kruskal-Wallis and Mann-Whitney non-parametric tests. Significance level was set at 0.05 for all analyses. RESULTS: µTBS data presented statistically lower values for groups D and B, ranking data as A>;C>;B>;D. The use of oxalic acid resulted in microleakage reduction along the tooth/restoration interface, being significant when used alone. On the other hand, the use of 10% NaOCl alone or in combination with oxalic acid, resulted in increased microleakage. CONCLUSIONS: Dentin deproteinization with 10% NaOCl or in combination with oxalate significantly compromised both the adhesive bond strength and the microleakage at interface. Tubular occlusion prior to adhesive system application seems to be a useful technique to reduce marginal microleakage.